The stamp technique for direct Class II composite restorations: A case series - Alshehadat, Saaid Ayesh; Halim, Mohamad Syahrizal; Koh, Carmen; Chew, Shi Fung (Medknow Publications, 2016)
Background: “Stamp” technique is a new method for placing large composite restorations with accurate occlusal topography. It was introduced mainly to restore Class I cavities and erosively damaged teeth. This technique is indicated when the preoperative anatomy of the tooth is intact and not lost due to the carious lesion. A precise tooth-like filling an accurate functional occlusion is obtained when the stamp technique is applied. However, using this technique to restore Class II cavities is not established yet. Aim: To introduce modifications of the stamp technique that make it applicable to restore Class II composite restorations. Materials and Methods: The traditional materials and tools used for direct composite restorations are needed with no additional instruments. Clinical illustrations and step-by-step description are provided in this paper. Results and Conclusion: Using the stamp technique to restore Class II cavities is achievable, simple and practical, and result in a very accurate anatomical restoration.